Fabrication of controllable and stable In2O3 nanowire transistors using an octadecylphosphonic acid self-assembled monolayer. (16th March 2015) - Lim, Taekyung; Han, Junebeom; Seo, Keumyoung; Joo, Min-Kyu; Kim, Jae-Sung; Kim, Wung-Yeon; Kim, Gyu-Tae; Ju, Sanghyun
Abstract: The controllability and stability of nanowire transistor characteristics are essential for the development of low-noise and fast-switching nano-electronic devices. In this study, the positive shift of threshold voltage and the improvement of interface quality on In2 O3 nanowire transistors were simultaneously achieved by using octadecylphosphonic acid (OD-PA) self-assembly. Following the chemical bond of OD-PA molecules on the surface of In2 O3 nanowires, the threshold voltage was positively shifted to 2.95 V, and the noise amplitude decreased to approximately 87.5%. The results suggest that an OD-PA self-assembled monolayer can be used to manipulate and stabilize the transistor characteristics of nanowire-based memory and display devices that require high-sensitivity, low-noise, and fast-response.